182k views
3 votes
Need help solving
-3^4x-3^4/(-3^2)^3

User Keaplogik
by
4.8k points

1 Answer

5 votes

Answer:

The solved given expression is


(-3^4x-3^4)/((-3^2)^3)=-((x+1))/(9)

Explanation:

Given expression is
(-3^4x-3^4)/((-3^2)^3)

To solving the given expression as below :


(-3^4x-3^4)/((-3^2)^3)


(-3^4x-3^4)/((-3^2)3)=(3^4(-x-1))/((-3^2)3)


=(-3^4(x+1))/((3^2)3) ( by using the property
(a^m)^n=a^(mn) )


=(-3^4(x+1))/(3^6)


=(-(x+1))/(3^6.3^(-4)) ( by using the property
a^m=(1)/(a^(-m)) )


=(-(x+1))/(3^(6-4)) ( by using the property
a^m.a^n=a^(m+n) )


=-((x+1))/(3^2)


=-((x+1))/(9)

Therefore
(-3^4x-3^4)/((-3^2)^3)=-((x+1))/(9)

Therefore the solved given expression is


(-3^4x-3^4)/((-3^2)^3)=-((x+1))/(9)

User Suxgri
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.